Identification of Tools for the Functional and Subjective Assessment of Patients in an Aquatic Environment: A Systematic Review - Cuesta-Vargas, Antonio; Martín-Martín, Jaime; González-Sánchez, Manuel; Merchán-Baeza, Jose Antonio; Pérez-Cruzado, David Francisco (MDPI, 2020)
Aquatic therapy is one of the most common treatments for alleviating musculoskeletal pathologies. Its effectiveness has been evaluated with functional tests and questionnaires. Functional tests are used in aquatic therapy; however, in most cases, they are carried out in a non-aquatic environment and, as such, their results may differ from those of tests performed in an aquatic environment. A systematic review was performed to assess the accuracy of functional tests and patient-reported outcomes to assess aquatic therapy interventions. The authors conducted a literature search in July 2019. In total, 70,863 records were identified after duplicates removed. Of these, 14 records were included about functional tests assessment in aquatic environment and 725 records for questionnaires. The majority of the tests had also been assessed in a dry environment, allowing differences and similarities between the tests in the two environments to be observed. Different variables have been assessed in tests included in the present systematic review (cardiorespiratory, neuromuscular, kinematic, physiological, kinetic responses and rating of perceived exertion) which are included in the manuscript. Visual Analogue Scale, Western Ontario and McMaster Universities Osteoarthritis Index and the 12-item Short Form Health Survey were the assessments most commonly used by the different authors.
Keywords: Hidroterapia; Aquatic therapy; Assessment; Functional test; Questionnaires